Mineral stress affects the cell wall composition of grapevine (Vitis vinifera L.) callus - Fernandes, João C. (2016)
Grapevine (Vitis vinifera L.) is one of the most economically important fruit crops in the world. Deficit in nitrogen, phosphorus and sulfur nutrition impairs essential metabolic pathways. The influence of mineral stress in the composition of the plant cell wall (CW) has received residual attention. Using grapevine callus as a model system, 6 weeks deficiency of those elements caused a significant decrease in growth. Callus CWs were analyzed by Fourier transform infrared spectroscopy (FT-IR), by quantification of CW components and by immunolocalization of CW epitopes with monoclonal antibodies. PCA analysis of FT-IR data suggested changes in the main components of the CW in response to individual mineral stress. Decreased cellulose, modifications in pectin methyl esterification and increase of structural proteins were among the events disclosed by FT-IR analysis. Chemical analyses supported some of the assumptions and further disclosed an increase in lignin content under nitrogen deficiency, suggesting a compensation of cellulose by lignin. Moreover, polysaccharides of callus under mineral deficiency showed to be more tightly bonded to the CW, probably due to a more extensive cross-linking of the cellulose–hemicellulose network. Our work showed that mineral stress impacts the CW at different extents according to the withdrawn mineral element, and that the modifications in a given CW component are compensated by the synthesis and/or alternative linking between polymers. The overall results here described for the first time pinpoint the CW of Vitis callus different strategies to overcome mineral stress, depending on how essential they are to cell growth and plant development